Pendidikan Dengan Pendekatan Marxis-Sosialis - Afifuddin, Afifuddin (Fakultas Adab dan Humaniora UIN Alauddin, 2015)
Marxism-Socialism is a theory which is designed to build a good society. A society that negates the suppression of one class against another class, the widest possible freedom for every person to express his humanity in any production activity (economic) as the basis of human life. Marxism balked patterns of education that only prepares participants to be workers who will be squeezed by the machinery of capitalist production. In view of Marxism, Practice, in the sense of direct relevance to the realities of human and material nature, is the criterion of truth, because it underlies the knowledge of reality and because of the outcome of cognitive processes is realized in the activity of the material, human objective. Practice is the sole criterion of objective truth, in so far as it represents not only mental human, but also human linkages that exist objectively with the natural and social world that surrounds him.